Systematic approach to measure the performance of microchannel-plate photomultipliers - Lehmann, Albert; Böhm, Merlin; Götz, Klaus; Gumbert, Katja; Krauss, Steffen; Miehling, Daniel; Pfaffinger, Markus (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2024)
In this paper, we present our approach to systematically measure numerous performance parameters of microchannel plate photomultiplier tubes. The experimental setups, the analyses and selected results are discussed. Although the techniques used may be different in other locations, the document is intended as a guide for comparable measurements with other types of microchannel plate photomultiplier tubes. Measurements are shown for the following performance parameters: spectral and spatial quantum efficiency, collection efficiency, gain as a function of voltage, position and magnetic field, time resolution, rate capability and lifetime. By using a dedicated 3-axis stepper and an FPGA-based data acquisition system, also inner PMT parameters are measured as a function of the active area, such as relative detection efficiency, dark count rate, time resolution, recoil electron and afterpulse distributions, as well as charge sharing and electronic crosstalk. In addition, some of the parameters are investigated inside a strong magnetic field. For many of these measurements, the change of most setup parameters and the subsequent analysis can be controlled semi-automatically by software scripts.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Afterpulses; Collection efficiency; Crosstalk; Dark count rate; Gain; Lifetime; Magnetic field; Multianode microchannel-plate PMTs; PANDA; Performance parameters; Quantum efficiency; Rate capability; Recoil electrons; Time resolution